LIVING WITH VITILIGO: IMPACT OF THE DISEASE ON THE INDIVIDUALS’ QUALITY OF LIFE (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Introduction: Vitiligo is a disease characterized by asymptomatic hypochromic and/or achromic macules, localized or generalized in the integumentary system. The visible depigmentation in the skin of the individual and usually exposed in daily life changes the body image, impacting their quality of life. Objective: To evaluate the quality of life of people living with vitiligo. Method: This is a cross-sectional study carried out with 86 individuals with vitiligo. For data collection, the Vitiligo-Specific Quality-of-Life Instrument questionnaire was used for quality of life. Results: Adult women (81.4%) (mean age 39 years old) with vitiligo had a medium impact on quality of life, and the factors that interfered with quality of life are related to intensified skin care, progression, and appearance of the disease. Conclusion: The vitiligo pathology interfered in the quality of life of adults. The factors that impacted quality of life were intensified skin care in leisure activities, the progression of the disease and the appearance of hypochromic spots.